Technology Transfer and Training on Making Adaptive Sticks to Instructors at SLBN-A Citeureup, Cimahi City to Improve the Mobility Orientation Ability of Students with Visual Disabilities - Ridwan Solihin; Budi Setiadi; Baisrum Baisrum; Siswoyo Siswoyo; Adnan Rafi Al Tahtawi; Heri Budi Utomo (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
All students and teachers with Visual Sensory Disabilities (PDSN) in the State Special School Category A (SLBN-A) Citeureup Cimahi City have been equipped with basic Mobility Orientation (OM) technical skills to be able to carry out independent activities and mobility. The OM technique uses five still-functioning senses: a white cane and a guide. Another problem from the assistant's side was that both class and dormitory teachers felt worried/anxious regarding PDSN students' whereabouts in the school environment. PKM's output for making sticks is focused on ergonomics, ease of installation, use, and functions that do not burden the PDSN. The stick will detect objects before you and inform you about them through sound (beep), vibration, or a combination. In implementing this PKM, the team carried out knowledge and technology transfer to the Instructors/Teachers as well as testing to the PDSN. This activity results in an electronic walking stick that has been tested.